Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd004450.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Desferrioxamine mesylate for managing transfusional iron overload in people with transfusion-dependent thalassaemia

Abstract: We found no reason to change current treatment recommendations. However, considerable uncertainty continues to exist about the optimal schedule for desferrioxamine in people with transfusion-dependent thalassaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…When administered in adequate doses it reduces iron overload, improves cardiac function and has been shown to reduce iron-related morbidity and mortality. 4 Unfortunately, compliance still remains a serious limiting factor in treatment success because of requirement of subcutaneous infusions and high cost. Vitamin C has been shown to increase the availability of cheatable iron and is given at the time of desferrioxamine infusion in the dose of 2-3 mg/kg/day.…”
Section: Desferrioxamine (Dfo)mentioning
confidence: 99%
“…When administered in adequate doses it reduces iron overload, improves cardiac function and has been shown to reduce iron-related morbidity and mortality. 4 Unfortunately, compliance still remains a serious limiting factor in treatment success because of requirement of subcutaneous infusions and high cost. Vitamin C has been shown to increase the availability of cheatable iron and is given at the time of desferrioxamine infusion in the dose of 2-3 mg/kg/day.…”
Section: Desferrioxamine (Dfo)mentioning
confidence: 99%
“…The ability of desferrioxamine to significantly reduce body iron burden has been repeatedly demonstrated. 29 However, in all the series reported, 65% of the patients treated with desferrioxamine alone were found to have a T2* in the midventricular septum less than 20 ms and, therefore, less than an optimal target. 30 These findings confirm a possible important difference in drug action: deferiprone seems to be a better agent for removing/preventing myocardial siderosis, but less effective in removing hepatocellular…”
mentioning
confidence: 93%
“…26 Deferasirox is a very effective chelator, but it is not superior to the other chelating drugs. 27 In a recently published study, long term follow-up of both adults and children showed good safety and efficacy of deferasirox in removing liver iron and reversed or stabilised liver fibrosis in 83% of the patients. 28 29 Furthermore, a longitudinal study in 39 patients showed that continuous treatment with deferasirox for two years, with a target dose of 40 mg/kg per day, continued to remove iron from the heart in patients with β thalassemia major and mild, moderate, or severe cardiac siderosis.…”
Section: How Should Iron Overload Be Prevented and Treated?mentioning
confidence: 96%